Tectono-stratigraphic evolution during rifting of the southwestern Australian margin - Olierook, Hugo K.H. (Curtin University, 2015)
Basin development and magmatism on the southwestern Australian margin are profoundly affected by continental breakup. Before and after breakup, sedimentary basins experienced regime switches in: fluvial-dominated to paralic sedimentation; paleo-drainage and provenance from south–north to east–west, and; locally heterogeneous subsidence and exhumation driven by tectonic events to more regionally homogeneous subsidence and exhumation driven predominantly by epeirogenesis. The breakup of eastern Gondwana resulted in coeval magmatism, driven by the Kerguelen mantle plume.